Hematopoietic stem cell transplantation for inborn errors of immunity: 30-year single-center experience - Dell’Orso, Gianluca; Bagnasco, Francesca; Giardino, Stefano; Pierri, Filomena; Ferrando, Giulia; Di Martino, Daniela; Micalizzi, Concetta; Guardo, Daniela; Volpi, Stefano; Sabatini, Federica; Miano, Maurizio; Gattorno, Marco; et al. (Frontiers in Immunology, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents an effective treatment for a variety of inborn errors of immunity (IEI). We report the experience of children affected by IEI who received allo-HSCT over a period of 32 years at IRCCS Istituto Giannina Gaslini, Genoa, Italy. HSCTs were performed in 67 children with IEI. Kaplan-Meier estimates of overall survival rate at 5 years in the whole group of patients was 83.4% after a median follow-up of 4 years. Median age at transplant was 2.5 years. 8 allo-HSCT were complicated by either primary or secondary graft failure (GF), the overall incidence of this complication being 10.9%. Incidence of grade 3-4 aGvHD was 18.7%, significantly lower in haploidentical transplant cohort (p=0.005). Year of transplant (≤2006 vs >2006) resulted the main factor in influencing outcome. In fact, a significant improvement in 5-year OS was demonstrated (92.5% >2006 vs 65% ≤2006, p=0.049). Frequency of severe aGvHD was significantly reduced in recent years (≤2006 61.5%, vs >2006 20%, p=0.027). A significant progress has been the introduction of the TCR αβ/CD19-depleted haploidentical platform, which was associated to absent severe aGvHD. However, it was associated with 23.5% incidence of GF. All but 1 patient experiencing GF in the whole cohort were successfully retransplanted. In summary, allo-HSCT is confirmed to be an effective treatment for children with IEI, even in absence of HLA-matched donor. Outcomes are improving in the last years, in particular due to the haploidentical αβ/CD19 depleted allo-HSCT, which guarantees low incidence of GvHD.